Myoclonic dystonia phenotype related to a novel calmodulin-binding transcription activator 1 sequence variant - Dzinovic, Ivana; Serranová, Tereza; Prouteau, Clement; Colin, Estelle; Ziegler, Alban; Winkelmann, Juliane; Jech, Robert; Zech, Michael (Neurogenetics, 2021)
Intragenic rearrangements and sequence variants in the calmodulin-binding transcription activator 1 gene (CAMTA1) can result in a spectrum of clinical presentations, most notably congenital ataxia with or without intellectual disability. We describe for the first time a myoclonic dystonia-predominant phenotype associated with a novel CAMTA1 sequence variant. Furthermore, by identifying an additional, recurrent CAMTA1 sequence variant in an individual with a more typical neurodevelopmental disease manifestation, we contribute to the elucidation of phenotypic variability associated with CAMTA1 gene mutations.
Keywords: Sequence Deletion; Dystonic Disorders; poruchy zraku; sekvenční delece; genetické asociační studie; fenotyp; Intellectual Disability; Male; Child, Preschool; Pedigree; rodokmen; Phenotype; Hearing Loss; nesmyslný kodon; Genetic Association Studies; sekvenování exomu; Adult; dystonické poruchy; dospělí; mužské pohlaví; předškolní dítě; trans-aktivátory; lidé; nedoslýchavost; Vision Disorders; ženské pohlaví; Humans; Calcium-Binding Proteins; proteiny vázající vápník; Codon, Nonsense; Trans-Activators; posunová mutace; Female; Exome Sequencing; Frameshift Mutation; mentální retardace